IT-adapted process optimisation in a dermatology ward on the example of an EDP-supported scheduling programme. - Folkers B (Pflegewissenschaft, 2008)
This text deals with process optimisation via IT technology in daily working practice. By the example of an EDP-supported scheduling programme instead of many handwritten calendars in the dermatology ward of the Clinical Centre Oldenburg gGmbH the facilitation of the daily practice through computerisation shall be demonstrated. The way of implementation beginning with the communication interface computer scientist DS health care professional will be outlined. Through the introduction of this dialogue the practical application of the entity-relationship model according to P.P. Chen will be introduced. Another step is the description of the planning and realisation of the employee training. Reservations of the employees as well as the particularities of adult education are being considered. Finally, the programme implementations' meaning for the ward's organisation development and the results will be discussed.